Red tape: developing and validating a new job-centered measure - Loon, Nina M. Van (2016)
Red tape studies typically focus on burdensome rules that have negative effects on organizations, as perceived by managers. The one-item general red tape scale is representative of this approach. However, scholars have called for improved measures that address the scale's shortcomings. This article introduces a new measurement scale that features (1) red tape as a two-dimensional construct that includes compliance burden and lack of functionality and (2) a job-centered approach that measures red tape as experienced by employees in their jobs rather than more generally in the organization. A set of survey questions derived from interviews with government employees was validated using data from 1,203 government employees. The findings indicate that the two-dimensional job-centered red tape scale is reliable and valid. The authors conclude that this measure can improve research and be used by managers for a "quick scan" to detect the location and severity of red tape. - Reproduced.
Keywords: Organizations; Bureaucracy